Fishing community preferences and willingness to pay for alternative developments of ecosystem‐based fisheries management (EBFM) for Lake Naivasha, Kenya. Issue 3 (9th July 2018) - Mulatu, Dawit W.; van Oel, Pieter R.; Odongo, Vincent; van der Veen, Anne
Abstract: Ecosystem‐based fisheries management (EBFM) is an important complement to existing fisheries management approaches to maintain ecosystem health and function; to translate goals and aspirations for sustainability into operational objectives, the preferences of the fishing communities should be considered for successful implementation of EBFM. This study analysed the preferences of the fishing community for alternative EBFM developments for Lake Naivasha, Kenya, and estimated the willingness to pay, using a choice experiment approach. Protection of fish breeding grounds, improving tilapia fish abundance and accessibility of fishing zones were identified as relevant EBFM attributes for the choice experiment. A monetary attribute (payment for fishing permit) was also included. In addition to a conditional logit model, mixed logit models are estimated to account for heterogeneity in preferences. This study results indicated fishing communities are most concerned about tilapia fish abundance and protection of fish breeding grounds. The welfare measures reveal that members of the Lake Naivasha fishing community are willing to pay a considerable sum of money for ecosystem services improvement, relative to their low income derived from fishing. These study findings highlighted that evaluating the preferences of the fishing community and valuing the fishery at an ecosystem level are vital to prioritize and choose between alternative interventions for sound implementation of EBFM.